3(5x+3)=-5(5x-2)

Simple and best practice solution for 3(5x+3)=-5(5x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(5x+3)=-5(5x-2) equation:


Simplifying
3(5x + 3) = -5(5x + -2)

Reorder the terms:
3(3 + 5x) = -5(5x + -2)
(3 * 3 + 5x * 3) = -5(5x + -2)
(9 + 15x) = -5(5x + -2)

Reorder the terms:
9 + 15x = -5(-2 + 5x)
9 + 15x = (-2 * -5 + 5x * -5)
9 + 15x = (10 + -25x)

Solving
9 + 15x = 10 + -25x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '25x' to each side of the equation.
9 + 15x + 25x = 10 + -25x + 25x

Combine like terms: 15x + 25x = 40x
9 + 40x = 10 + -25x + 25x

Combine like terms: -25x + 25x = 0
9 + 40x = 10 + 0
9 + 40x = 10

Add '-9' to each side of the equation.
9 + -9 + 40x = 10 + -9

Combine like terms: 9 + -9 = 0
0 + 40x = 10 + -9
40x = 10 + -9

Combine like terms: 10 + -9 = 1
40x = 1

Divide each side by '40'.
x = 0.025

Simplifying
x = 0.025

See similar equations:

| v+60=5v | | 3x+90=126 | | 6x=9y-6 | | 0.6(b-4)=-9 | | 8x-2y=41 | | 1.82= | | x(x+12)=(x-4)(x-4) | | ln(5x)+ln(10x)=4 | | 4-v=265 | | 6x+9y=65 | | Y-4+7y=24 | | -16=-4+4y | | y-7.2=9 | | 8x-(11x-9)=24-3x | | X-17=3Y-17 | | a+5=6a | | 75+2y=42 | | 3v=v+38 | | 40.00+19.25x=69.25+16.00x | | ln(7)+ln(x+3)=0 | | y=2x-(-3) | | 9cot^2-3=0 | | 5(3n+1)=7(4n+5)+5 | | 5/3y--10 | | 5(3g+4h)= | | cos(30x)=x/8 | | -10.1q=-80.1-1.2q | | x-30=-4x+15 | | 5pints=liter | | x-30=4x+15 | | 9a(ab+3)(3ab-2)= | | x^(3/4)-x^(1/4) |

Equations solver categories